The Role for Invasive Monitoring in Acute Lung Injury - Martin, Greg S. (Seminars in Respiratory and Critical Care Medicine, 2013)
Because acute lung injury (ALI) may arise from diverse and heterogeneous clinical insults, monitoring strategies for patients with ALI are heterogeneous as well. This review divides the monitoring strategies for ALI into three distinct phases. The “at-risk phase” is the period in which patients are at risk for ALI, and interventions may be applied to minimize or eliminate this risk. The “ALI phase” is the period during which ALI has occurred and requires attentive clinical management. The “resolution phase” is the period defined by resolution of ALI and successful discontinuation of mechanical ventilation. These phases are arbitrary, but they provide a useful framework for discussing the temporal changes in patient condition and monitoring goals in ALI.Invasive hemodynamic monitoring has specific roles in each phase of therapy for patients with ALI: pre-ALI, peri-ALI, and post-ALI. The primary goals are to optimize fluid resuscitation to prevent organ dysfunction, including ALI, and if ALI occurs to additional optimize fluid balance vis-à-vis the lung. By judicious application of invasive hemodynamic monitoring, particularly in its more modern iterations, clinicians can optimize the ebb and flow phases common to critically ill patients. This is vitally important given our current and growing understanding of the relationship between fluid balance and important clinical outcomes, multiple organ dysfunction syndrome, and mortality.
Keywords: acute lung injury; hemodynamic monitoring; fluid resuscitation; early goal-directed therapy (EGDT); pulmonary artery catheter; cardiac output